Leaf decomposition of the macrophyte Eichhornia azurea and associated microorganisms and invertebrates - Da Silva, C. Vieira [UNESP]; Bianchini, I.; Gonçalves, J. F.; Oliveira, R. A. [UNESP]; Henry, R. [UNESP] (Springer Nature, 2018)
The knowledge of the decomposition of macrophytes and associated organisms is important to understand ecological processes that control aquatic ecosystem metabolism. The aims of the study were: 1) to investigate the structure and composition of the aquatic invertebrate community associated with the decomposition of leaves of the macrophyte Eichhornia azurea over time; 2) to determine the biomass of microorganisms (fungi and bacteria) and their relationship with the associated invertebrate communities; and 3) to assess the relationship between biotic and abiotic variables and invertebrate density. To analyze the decomposition process, leaves of E. azurea were put into litter bags and incubated in Barbosa Lake, São Paulo State, Brazil. Litter bags were retrieved at seven sampling occasions during a 2.5 month period. We measured decomposition rates of leaves, and the associated communities of invertebrates, the biomass of bacteria and fungi, and biotic and abiotic variables that might be associated with the decomposition process. Significant differences were found in the densities of invertebrates. The microorganism biomass also varied significantly throughout the experiment. Fungal biomass (ergosterol concentration) was positively associated with the density of most taxonomic groups of aquatic invertebrates, as well as the total density of invertebrates and their taxonomic richness. Total invertebrate density increased during the experiment, but the taxonomic richness of invertebrates did not follow this pattern. Insecta and Crustacea densities were the main contributors to similarity within the groups formed at each sampling time. The different ways that invertebrates use detritus, such as a food source or a feeding site, as well as their feeding plasticity, may have contributed to the increase in the total invertebrate density over time as decomposition progressed. After two months and a half of macrophyte incubation the loss of E. azurea leaf biomass was less than 4.4% of the initial value. Factors such as decreasing temperature throughout the experiment, possible inhibition of microorganism growth by leachates, the predominantly oligotrophic environment and low abrasion due to the environment lentic regime may have contributed to the low rate of decomposition of E. azurea. Our results suggest that decomposition process in the present study has not begun in fact and/or macrophyte decomposition in nature is much slower than previously thought.
Keywords: Aquatic insects; Aquatic macrophytes; ATP; Ergosterol; Lake